Back To The Future: Is The Travel Buble Issue In Malaysia Will Sustain The Region Tourism Outbreak Of Covid-19? - Arman Hj. Ahmad; Sheikh Muhamad Hizam Sheikh Khairudin; Zulkifli Saidun; Ilham Sentosa; Farah Hida Sharin; Mohd Juraij Abdul Rani (Cita konsultindo, 2025)
The current study aimed to determine the current travel bubble issue on the tourism marketing sustainability in Malaysia during the outbreak of COVID-19. To collect questionnaires, SPSS 28.0 software was used for statistical validation. The results were validated using multivariate analysis after expert opinions were gathered. A total of 206 respondents contributed to the questionnaire survey and data collected were analyzed using Smart-PLS. Based on the key-findings, this study found that people were aware of the virus's occurrence and preventive measures, but they were not afraid of infection. Tourists mostly want to have free time to travel as it can boost their energy, relieve stress from staying at home, and help their emotions. Unfortunately, due to the Pandemic COVID-19, the infection rates and death are high, and also there have been multiple routes of infection and the evolution of new variants recently namely omicron and identifying the symptoms has been difficult. However, people arriving and departing from airports, hotels et cetera, are the tourists who are willing to contribute to the travel bubble policy and travelling during this Pandemic COVID-19. Thus, travel decisions, environmental risk perceptions, physical and mental health and health beliefs were all significantly related to travel intentions, with different issues having various degrees of influence, whereas health beliefs had no effect. Further research is presented in this study.